The Holocaust: the fire that raged - Seymour, Rossel (Franklin Watts new York, 1989)
Discusses the historical background, from the Treaty of Versailles through Hitler's rise to power, that led to the horrible and systematic slaughter of millions of Jews by the Nazis during World War II.
Includes Index
Keywords: (1939-1945); 1933-1945